Under cover: detecting the existence of profit-shifting in China - Xuefeng Qian; Bifei Tian; W. Robert Reed; Ziruo Chen (Kiel Institute for the World Economy (IfW), 2017)
This paper investigates profit-shifting behaviour among a large sample of multinational corporations (MNCs) in China. While profit-shifting behaviour is difficult to observe directly, it can be inferred from the behaviour of firms. That is the approach taken by Egger, Merlo, and Wamser (Unobserved tax avoidance and the tax elasticity of FDI 2014, henceforth EM&W) in their seminal analysis of tax elasticity of German MNCs. They developed a two-component mixture model that categorized MNCs into tax "avoiders" and "non-avoiders" based upon the estimated elasticities of investment to taxes. The authors of this paper apply their approach to their sample of MNCs in China. Like EM&W they find evidence of two distinct groups of MNCs. One group is responsive to changes in taxes, reducing investment when taxes increase. The other group is unresponsive to taxes, so that investment is not significantly associated with changes in tax rates. The authors show that the characteristics of these groups closely match the "avoiders" and "non-avoiders" of EM&W's sample. Even so, their estimated tax elasticities are much smaller than EM&W. This suggests that the extent of profit-shifting was relatively small during China's period of preferential tax treatment for foreign investors.
Keywords: F23; H32; 330; MNCs; profit shifting; tax elasticity of investment; finite mixture model; China